Aggression Dimensions Among Athletes Practising Martial Arts and Combat Sports - Kostorz, Karolina; Sas-Nowosielski, Krzysztof (Frontiers in Psychology, 2021)
Purpose. The main aim of the research was to analyse aggression dimensions among athletes practising martial arts and combat sports. Material and Methods. There were 219 respondents. The Buss and Perry Aggression Questionnaire (BPAQ) in the Polish adaptation by Siekierka (2005) was applied. Results. Martial arts apprentices turned out to present a statistically significantly lower level of hostility (p < 0.001) and of the general aggression index (p = 0.04) than combat sports athletes. It turned out that lower level of aggression was noted in female participants (physical aggression (p < 0.001), verbal aggression (p = 0.004), hostility (p < 0.001) and the general aggression index (p < 0.001). Analysis revealed that the training experience and the training rank did not differentiated the level of the respondents’ particular aggression dimensions. Conclusions. It would be advisable to perform parallel analyses in other areas of Poland and take into account the respondents’ education and place of residence.